2018
DOI: 10.4143/crt.2017.494
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Pancreatic Cancer Patients with Synchronous or Metachronous Malignancies from Other Organs Is Better than Those with Pancreatic Cancer Only

Abstract: PurposePancreatic cancer associated double primary tumors are rare and their clinicopathologic characteristics are not well elucidated.Materials and MethodsClinicopathologic factors of 1,352 primary pancreatic cancers with or without associated double primary tumors were evaluated.ResultsOf resected primary pancreatic cancers, 113 (8.4%) had associated double primary tumors, including 26 stomach, 25 colorectal, 18 lung, and 13 thyroid cancers. The median interval between the diagnoses of pancreatic cancer and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 15 publications
2
40
1
1
Order By: Relevance
“…In a series of 113 patients with PDAC and double primary tumors, 44 patients (38.9%) were identified as having synchronous double primary tumors and 69 (61.1%) were diagnosed with metachronous double primary tumors [7]. The stomach was the most common location for a double primary with 26 patients, accounting for 21.5% of the 113 patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a series of 113 patients with PDAC and double primary tumors, 44 patients (38.9%) were identified as having synchronous double primary tumors and 69 (61.1%) were diagnosed with metachronous double primary tumors [7]. The stomach was the most common location for a double primary with 26 patients, accounting for 21.5% of the 113 patients.…”
Section: Discussionmentioning
confidence: 99%
“…These patients also had a higher overall survival (OS) compared to those with resected PDAC and synchronous double primary tumors. Patients who were diagnosed with PDAC before the metachronous double primary tumors have also been shown to have better survival [7]. Interestingly, pancreatic cancer patients with stomach, thyroid, and lung cancers have had better odds of survival ratios than those with pancreatic cancer only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although pancreatic cancer with double primary tumors seems to be a rare occurrence, data reports that this event raises an incidence variable from 0.75% to 20.0% [2][3][4][5]. In particular, in a study evaluating the incidence of locations of PDAC-associated double primary tumors, Shin et al discovered that most common hystologies were found in stomach (21.5%), colorectum (20.7%), and lung (14.9%) [2]. Interestingly, in this study, PDAC plus NSCLC patients had a tendency for a longer survival than those with pancreatic cancer only(median, 27.4 months vs. 17.0 months; p=0.092).…”
Section: Discussionmentioning
confidence: 99%
“…The Surveillance, Epidemiology, and End Results (SEER) Program indicates that multiple primary malignancies comprised a percentage that went from 1% for an initial liver primary diagnosis to 16% for initial bladder cancer primaries [1]. In particular, pancreatic ductal adenocarcinoma (PDAC) associated to double primary tumors show an incidence variable from 0.75% to 20.0% [2][3][4][5].The management of these clinical situations is a critical issue due to the lack of data with exception of single cases or small series [6][7][8]. So far, a patient-oriented approach would be advisable with the choice of therapies active against the tumor with the worse prognosis or active for both cancers.…”
Section: Introductionmentioning
confidence: 99%